Corresponsabilidad parental de padres separados en el cuidado y protección de un hijo con discapacidad a la luz de la normativa ecuatoriana - Cifuentes Ayala, Anahi Alejandra (2024)
The present investigation entitled Parental co-responsibility of separated parents in the care and protection of a child with disabilities considering Ecuadorian regulations, was based on previous investigations with similar topics from different approaches, and the constitutional, international, and lower hierarchy legal regime. which facilitated the understanding of the topic. Its general objective was to describe the application of the right/duty of parental co responsibility of separated parents in the care, upbringing, and protection of a child with disabilities considering Ecuadorian regulations, to demonstrate the application of the duty of parental co-responsibility in the Judicial Unit for Family, Women, Children and Adolescents of the Ibarra canton. It is a mixed study, documentary bibliographic modality, its level of depth was descriptive, the socio-legal method and the analytical method were applied. The results indicate that the application of the general regulations regarding parental co-responsibility with a disabled child facilitates discretion and lack of uniqueness in judicial resolutions. Parental co-responsibility is not equitable since the parent who has custody assumes greater responsibilities to guarantee the well-being and quality of life of his/her disabled child. It is the obligation of the State to collect information, verify the living conditions, support needs and social help required by the person with disabilities and their family environment, who are going through situations such as stress, depression, work, and economic problems. They are a vulnerable sector of the population that must receive state support in every way.